2023
DOI: 10.1093/jsxmed/qdac025
|View full text |Cite
|
Sign up to set email alerts
|

The association between sexual dysfunction and prostate cancer: a systematic review and meta-analysis

Abstract: Background Whether there is a connection between sexual dysfunction (SD) and prostate cancer (PCa) is controversial. Aim We sought to review the interrelationship between SD and PCa and to determine whether there is a definitive risk of men developing PCa after suffering from SD. Methods A complete search of the PubMed, Web of Science, Ovid MEDLINE, Embase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The development and progression of ED is directly and indirectly influenced by a variety of cancers, particularly prostate cancer. Radical prostatectomy and prostate radiation therapy can cause ED,45 46 and ED is a potential cause of prostate cancer 47. Although we excluded prostate cancer patients from our study, it is not clear whether the telomere length in some ED patients is altered by the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and progression of ED is directly and indirectly influenced by a variety of cancers, particularly prostate cancer. Radical prostatectomy and prostate radiation therapy can cause ED,45 46 and ED is a potential cause of prostate cancer 47. Although we excluded prostate cancer patients from our study, it is not clear whether the telomere length in some ED patients is altered by the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Radical prostatectomy and prostate radiation therapy can cause ED, 45 46 and ED is a potential cause of prostate cancer. 47 Although we excluded prostate cancer patients from our study, it is not clear whether the telomere length in some ED patients is altered by the development of cancer. Moreover, the impact of other prostate diseases on the interaction between the LTL and ED deserves consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Связь между артериальной гипертензией и сексуальной дисфункцией. Аг является широко распространённым заболеванием и известным фактором риска сексуальной дисфункции как у мужчин, так и у женщин [25,26]. несмотря на неоспоримые успехи в развитии фармакологической терапии Аг и широкое назначение антигипертензивных препаратов, лишь небольшая часть пациентов достигает стабильного поддержания целевых уровней Ад [27].…”
Section: результатыunclassified
“… 5 In the field of urology and andrology medicine, several previous studies have indicated a correlation between prostate disease and ED, 6 , 7 suggesting the presence of shared underlying factors. 8 In patients with prostate cancer (PCa), the presence of inflammation and increased levels of reactive oxygen species are linked to reduced blood flow necessary for achieving a penile erection. 9 In addition, various treatment options currently available, such as radical prostatectomy and radiotherapy, carry the risk of causing ED.…”
Section: Introductionmentioning
confidence: 99%